To solve the equation \(11x = 3(7x - 1) - 10x\), let's start by simplifying the right side.
-
Distribute the 3 on the right side: \[ 3(7x - 1) = 21x - 3 \]
-
Substitute this back into the equation: \[ 11x = 21x - 3 - 10x \]
-
Combine like terms on the right side: \[ 21x - 10x = 11x \implies 11x - 3 \]
-
Now, we have the equation: \[ 11x = 11x - 3 \]
-
Next, let's subtract \(11x\) from both sides: \[ 11x - 11x = 11x - 3 - 11x \] \[ 0 = -3 \]
Since the equation simplifies to \(0 = -3\), which is a contradiction, this means there are no values of \(x\) that satisfy the original equation.
Thus, the conclusion is that the equation has no solution.